A comparative study of life events in depressive patients and schizophrenia (Panacea Journal of Medical Sciences, 2024)
Introduction: The etiology of psychiatric illnesses is mostly multifactorial. Role of life events preceding the onset of depressive disorders is well known while the role of life events in schizophrenia is a topic of debate since decades. In this study, we aim to compare the presence of life events before the onset of illness in both these diagnostic categories, among a rural population in South India.Materials and Methods: This study was done in a tertiary medical centre in rural India, after getting ethical clearance from the institution. Participants in both groups were enrolled after getting informed consent. A semi-structured questionnaire was used to collect the socio-demographic details. Presumptive stressful life events scale (PSLES) was used to collect data from participants from both the groups, each containing 46 participants who were meeting the inclusion and exclusion criteria. Data was entered in Microsoft excel and analyzed using Epi-info software. Z-test was used for statistical measurements.Result: The presence of stressful life events before the onset of illness was significantly higher in the depression group. The average time lag between the stressor and onset of the disorder was around 2.74 months in the depression group while it was around 5.54 months in the schizophrenia group. The most commonly reported life events were family conflict, large loan, marital conflict, son or daughter leaving home and illness in family members.Conclusion: Although literature suggests that life events play an important role in precipitation and relapse of psychiatric disorders, this relationship is not straight forward. The relationship between stress and illness varies with preexisting vulnerability factors. Stress management, healthy living habits, skill training for all individuals should be emphasized on to strengthen coping skills. Future research may focus on other intervening variables in order to reduce the incidence of stress induced illnesses.